2014
DOI: 10.9734/ijtdh/2013/2606
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis in Ipogun: Update Assessment on Endemicity and Efficacy of Praziquantel in Chemotherapy

Abstract: This work was carried out in collaboration between all authors. Author MOO designed the study, performed the statistical analysis, wrote the protocol, and wrote the first draft of the manuscript. Authors MAI and ODJ managed the analyses of the study and the literature searches. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
1
15
2
Order By: Relevance
“…More so, females had a higher rate of prevalence than the males, which is contrary to previous studies in the same community where males were observed to have higher rate of prevalence than the females (Oniya et al, 2013) and in Edo state by Ugbomoiko (2000). This thus shows that it is the frequency of contact with an infected body of water and not their gender that determines the rate of transmission.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…More so, females had a higher rate of prevalence than the males, which is contrary to previous studies in the same community where males were observed to have higher rate of prevalence than the females (Oniya et al, 2013) and in Edo state by Ugbomoiko (2000). This thus shows that it is the frequency of contact with an infected body of water and not their gender that determines the rate of transmission.…”
Section: Discussioncontrasting
confidence: 98%
“…The overall prevalence rate of S. haematobium was far higher than the prevalence rate recorded in the same Ipogun community the previous year by Oniya et al (2013), considering the fact that this area receives praziquantel on a annual basis, prevalence would be expected to be lower than what was obtained. This persistent high prevalence could be the result of constant contact with the river which acts as source of infection since most of the bore holes dug by the State government are no longer functional, or perhaps due to reduced sensitivity of the parasite to drug regimen.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Duncan's New Multiple Range Test at (p≤0.05). [19,20] who in their study on the assessment of edemicity of prazinquatel where Ipogun-Ayo had the highest prevalence of 18.0%. This present study also implicated Ipogun-Ayo to have the highest prevalence of (28.72%).…”
Section: Difference Between Means Was Determined Bymentioning
confidence: 98%